Modeling and evaluating the effectiveness of AR advertising and the moderating role of personality traits. Issue 4 (19th May 2022) - Uribe, Rodrigo; Labra, Rafael; Manzur, Enrique
Abstract: This paper examines the effectiveness of AR ads vs. traditional ones, differentiating the effects of two types of AR advertisements (ARH and QRH), and the moderating effects of three personality traits on consumer evaluation of ARA. A sample of 173 individuals was exposed to either traditional or AR advertising (ARH or QRH). Results showed the superiority of AR ads over traditional ones in terms of ad reception, brand attitude and purchase intention. Regarding the moderating role of personality traits, it was observed that each one moderated a different aspect of ad reception: extraversion to entertainment perception, neuroticism to informativeness evaluation, and openness to experience to general ad attitude. Finally, some differences were detected between ARH and QRH: the former was superior, but only via entertainment, ad attitude, brand attitude and purchase intention. Results are discussed in terms of their conceptual and practical implications.